Pentingnya E-Commerce terhadap Penjualan Baby Shop di Surabaya - Veronika Nugraheni Sri Lestari; Devi Mei Ariyanti; Dwi Cahyono (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Currently the internet has become part of the needs of daily life, whose initial function was only limited to being a medium for exchanging information, but now slowly shifting into a new media capable of being an economic driver. This development is then used by business people to market their products. online in order to maintain its existence. Likewise, Liana Baby Shop, which acts as a retail store, which carries out sales activities for products related to mother and child equipment, posting pictures of its products on various marketplaces and social media. The method used in this service is carried out by observing and implementing directly in the field to obtain the data and information needed, namely at the baby shop directly, namely in the service section. The result of this service is being able to recognize baby shop products that will be marketed using e-commerce, and an increase in sales of baby shop products which is marked by the increasing number of orders for baby shop products